Pengaruh Impor Beras Terhadap Fluktuasi Ekonomi di Indonesia - Chaerani, Albina; Syafhiah, Fatma Bara; Yudha, Putry Adinda (PT Maju Malaqbi Makkarana, 2024)
This study aims to analyze the impact of rice imports on economic fluctuations in Indonesia, particularly in terms of price stability and farmer welfare. As a staple food, rice plays a strategic role in the national economy but is vulnerable to various challenges such as extreme weather, land conversion, and technological limitations that affect crop yields. In certain conditions, rice import policies are implemented to maintain stock availability and control inflation. This study employs a descriptive quantitative method with secondary data analysis derived from official reports and academic journals. The findings indicate that rice imports significantly affect national economic dynamics, including balancing supply and demand. However, these policies also suppress grain prices and negatively impact local farmers' incomes. Therefore, balanced policies, including support for local production, are needed to ensure long-term food security and economic stability in Indonesia.